2007
DOI: 10.2118/100666-pa
|View full text |Cite
|
Sign up to set email alerts
|

Operational Control of Hydrocyclones During Variable Produced Water Flow Rates—Frøy Case Study

Abstract: International regulations of produced water discharges to sea are enforced, thereby enhancing focus on optimizing produced water treatment. De-oiling hydrocyclones are prioritized technology for produced water treatment on offshore oil-producing platforms. Oil/ water separation happens within a few seconds in hydrocyclones and preciseness in operational control is essential. Surging flow may cause severe problems to hydrocyclones. A case study at TOTAL E&P NORGE AS's Frøy field demonstrated how the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…It is quite clear that the operational hydrocyclone efficiency is directly determined by the operational inflow rates and the inside flow-splits, which both need to be properly regulated by the hydrocyclone's operational control system [4], [16], [23], [44].…”
Section: B Hydrocyclone Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite clear that the operational hydrocyclone efficiency is directly determined by the operational inflow rates and the inside flow-splits, which both need to be properly regulated by the hydrocyclone's operational control system [4], [16], [23], [44].…”
Section: B Hydrocyclone Efficiencymentioning
confidence: 99%
“…Furthermore, from Fig.6 it can be noticed that the assumed linear relationship is very rough if we intend for much more precise hydrocyclone control than any current PID solution. It is noticed that the hydrocyclone efficiency is evaluated by the oil concentration in samples from experimental tests in [15], [16], [17], though the accuracy of this type of sampling is quite uncertain. Moreover, it has been observed in [15], [17] that for different inflow rates, the efficiency drifted even though PDR is still kept around the set-point.…”
Section: E Other Concerned Issuesmentioning
confidence: 99%
“…The spinning of the fluid develops a vortex within the body of the cyclone thereby creating a strong gravity field. Fluids with different densities in this gravity field move in radial opposite directions (Husveg et al [5]). The swirling movement of the fluid increases the centrifugal force which causes the heavier water fraction to migrate to the walls of the cyclone whereas the lighter oil fraction is displaced to form a low central core [2,3].…”
Section: The Llhc Basismentioning
confidence: 99%
“…A Piping and Instrumentation Diagram (P&ID) of the de-oiling system that is considered in this study can be seen in Figure 1. In previous work, it was shown that such a system is sensitive towards fluctuating inlet flow rate [15,[18][19][20], which is a re-occurring phenomenon in such installations and in most occasions it is caused by slugging flow regime in the upstream pipeline system [21][22][23]. An investigation of the offshore data, as shown in Figure 2, shows a typical performance of a conventional de-oiling controller, consisting of two individual PID controllers, a level and a PDR controller, as shown in Figure 1, during a fluctuating inlet flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the explicit reference tracking of the PID, and especially the level control structure, amplifies the disturbance transmission through the system, i.e., the inlet flow rate to the gravity separator is transmitted to the hydrocyclone, which affects the de-oiling systems performance as discussed in [24,27,28]. Thus, as in most cases, the inlet flow rate is not directly measured, and the flow rate in some cases is only a part of a secondary objective, the flow through the hydrocyclone varies with the gravity separator inlet flow rate [18]. We believe that the performance of the de-oiling system can be improved upon by introducing a new control solution that addresses some of the aforementioned challenges.…”
Section: Introductionmentioning
confidence: 99%